Split Applications of Acuron, Halex GT, Resicore, Balance Flexx, and Armezon Pro for Weed Control in Irrigated Corn - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2018)
Control of kochia, green foxtail, quinoa, and Palmer amaranth was excellent and did not differ among treatments. Common sunflower control was slightly less effective with Acuron (S-metolachlor + atrazine + mesotrione + bicyclopyrone) + atrazine applied PRE compared to other treatments early in the season but later in the season no differences occurred. Crabgrass control was excellent regardless of treatment early in the season, and remained high with all herbicides except Balance Flexx (isoxaflutole) + atrazine PRE followed by Diflexx (dicamba) + atrazine and glyphosate POST, which provided less than 89% control. All herbicide treatments resulted in grain yields that were 67 to 101 bu/a greater than the untreated controls. The best herbicide treatment yielded 34 bu/a more than the lowest yielding herbicide combination.
Keywords: Residual control; sequential application